Competitiveness of the potato sector in Colombia: analysis from a macro perspective for the period 2000-2012 - Monroy-Medina, Germán Andrés; Suárez-Pineda, Marlen; Lopez-Ruiz, Yemina Paola (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Globalization has led to the creation of a global market, where competition plays a key role. The absence of a business environment that can be effective to achieve structural competitiveness has led efforts to collectively build an environment that involves companies, the State, associations, and other stakeholders, translating this interaction into the capacity of the production sector to participate in the dynamics of global markets.This is an analysis of the interaction between certain variables and their impact on the competitiveness of the potato sector in Colombia made under the concept of systemic competitiveness. There have been five variables, one of them considered dependent: the participation rate on the market, others such as: per capita consumption, trade balance, exchange rate, GDP per capita provide a pressure on the first, which causes an increase or a decrease in the competitive condition of the sector.